Changes in Parent, Sibling, and Peer Support During the Transition to Young Adulthood. (8th January 2015) - Guan, Shu‐Sha Angie; Fuligni, Andrew J.
Abstract : Longitudinal trajectories of parent, sibling, and peer support during the transition to young adulthood were compared among 600 participants (51.1% female) from Asian, European, and Latin American backgrounds. Participants completed questionnaires at 12th grade, 2 and 4 years after high school. Results indicated that parent support increased across this period for participants from European backgrounds but remained stable for participants from Asian and Latin American backgrounds. Peer and sibling support remained relatively stable. Supports had specific implications for self‐esteem and depressive mood. On average, young adults with higher levels of support reported greater expectations to reciprocate support within the family. Together, these findings highlight the changing dynamics of family and friends during the transition to young adulthood.